Corneal Backscatter Analysis by In Vivo Confocal Microscopy: Fellow Eye Comparison of Small Incision Lenticule Extraction and Femtosecond Laser-Assisted LASIK. (5th March 2014) - Agca, Alper; Ozgurhan, Engin Bilge; Yildirim, Yusuf; Cankaya, Kadir Ilker; Guleryuz, Nimet Burcu; Alkin, Zeynep; Ozkaya, Abdullah; Demirok, Ahmet; Yilmaz, Omer Faruk
Abstract : Purpose . To evaluate and compare corneal backscatter from anterior stroma between small incision lenticule extraction (SMILE) and femtosecond laser-assisted LASIK (femto-LASIK). Methods . A cohort of 60 eyes of 30 patients was randomized to receive SMILE in one eye and femto-LASIK in the fellow eye. In vivo confocal microscopy was performed at 1 week and 1, 3, and 6 months after surgery. The main outcome measurements were maximum backscattered intensity and the depth from which it was measured, the backscattered light intensity 30 μ m below Bowman's membrane at the flap interface and 150 μ m below the superficial epithelium, and the number of refractive particles at the flap interface. Results . The mean backscattered light intensity (LI) at all measured depths and the maximum backscattered LI were higher in the SMILE group than the femto-LASIK group at all postoperative visits. LI differences at 1 week and 1- and 3-month visits were statistically significant (P < 0, 05). LI differences at 6 months were not statistically significant. There was no difference in the number of refractive particles at the flap interface between the groups at any visit. Conclusions . SMILE results in increased backscattered LI in the anterior stroma when compared with femto-LASIK were evaluated.